Analysis of the Contact Stresses in Curvic Couplings of Gas Turbine in a Blade-Off Event - Jiang, X.-J.; Zhang, Y.-Y.; Yuan, S.-X. (Проблемы прочности, 2012)
The contact pressure distribution of the curvic couplings in a heavy duty gas turbine under a blade-off load condition is investigated in a three-dimensional finite element model. Several blade-off positions on each stage disc may develop the different characters on the contact pressure distributions of the curvic couplings during the application of a blade-off load. Both the position and magnitude of the applied blade-off load and the distribution of the spindle bolts have an effect on the contact pressure distribution of the curvic couplings. Further the contact stress on the left and right sides of the teeth develops different characters during the application of torque load following not only a normal centrifugal load but also a blade-off load which produces an unbalanced equivalent bending force. Furthermore the stiffness of the connection body part of the rotor between the compressor end and the turbine end associated with its section thickness is crucial in deciding the contact stress distribution on the curvic couplings. This analysis shows a change in the magnitude of contact stress of each set of the curvic couplings. С помощью трехмерной конечноэлементной модели исследовано распределение контактных напряжений в криволинейных сочленениях высоконагруженной газовой турбины в условиях, соответствующих случаю отрыва лопатки. Для разных положений оторвавшихся лопаток на диске каждой ступени распределение контактных напряжений в криволинейных сочленениях в случае приложения усилий, соответствующих отрыву лопатки, различается. При этом точка приложения и величина усилия, а также распределение усилий затяжки болтов крепления оказывают существенное влияние на распределение контактных напряжений. Кроме того, характер изменения контактных напряжений как с одной, так и с другой стороны зуба сочленения при наличии крутящего момента различается из-за усилия, обусловленного отрывом лопатки. Помимо нормальной центробежной силы возникает неуравновешенная изгибающая сила. Показано, что жесткость сочленяемой части ротора между торцами компрессора и турбины, определяемая жесткостью его сечения, оказывает влияние на распределение контактных напряжений в криволинейных сочленениях. Выполнен расчет жесткости для каждого из таких сочленений. За допомогою тривимірної скінченноелементної моделі досліджено розподіл контактної напруги в криволінійних з єднаннях високонавантаженої газової турбіни в умовах, що відповідають випадку відриву лопатки. Для різних положень лопаток, що відірвалися, на диску кожного ступеня контактна напруга у криволінійних з єднаннях у випадку прикладення зусиль, що відповідають відриву лопатки, розподіляється по-різному. При цьому точка прикладення і величина зусилля, а також розподіл зусиль затягнення болтів кріплення суттєво впливають на розподіл контактних напруг. Окрім того, характер зміни контактних напруг як з однієї, так і з іншої сторони зуба з єднання при крутному моменті різний через зусилля, яке зумовлене відривом лопатки. До нормальної відцентрової сили додається неврівноважена згинальна сила. Показано, що жорсткість з єднання частини ротора між торцями компресора і турбіни, що визначається жорсткістю його перерізу, має вплив на розподіл контактних напруг у криволінійних з єднаннях. Проведено розрахунок жорсткості для кожного з таких з єднань.